The development and validation of the King's Sarcoidosis Questionnaire for the assessment of health status. Issue 1 (12th October 2012) - Patel, Amit Suresh; Siegert, Richard J; Creamer, Daniel; Larkin, Genevieve; Maher, Toby M; Renzoni, Elisabetta A; Wells, Athol U; Higginson, Irene J; Birring, Surinder S
Abstract : Rationale: Health status is impaired in patients with sarcoidosis. There is a paucity of tools that assess health status in sarcoidosis. The objective of this study was to develop and validate the King's Sarcoidosis Questionnaire (KSQ), a new modular health status measure. Methods: Patients with sarcoidosis were recruited from outpatient clinics. The development of the questionnaire consisted of three phases: item generation; item reduction, Rasch analysis to create unidimensional scales and validation; repeatability testing. Results: 207 patients with sarcoidosis (organ involvement: 184 lung, 54 skin, 45 eye disease) completed a 65-item preliminary questionnaire. 36 items were removed due to redundancy or poor fit to the Rasch model. The final version of the KSQ consisted of five modules (General health status, Lung, Skin, Eye, Medications). Internal consistency assessed with Cronbach's α coefficient was 0.70–0.93 for KSQ modules. Concurrent validity of the Lung module was high compared with St George's Respiratory Questionnaire (r=−0.83) and moderate when compared to forced vital capacity (r=0.49). Concurrent validity with skin-specific and eye-specific measures ranged from r=−0.4 to 0.8. The KSQ was repeatable over 2 weeks (n=39), intraclass correlation coefficients for modules were 0.90–0.96. Conclusions: The KSQ is a brief, valid, self-completed health status measure for sarcoidosis. It can be used in the clinic to assess sarcoidosis from the patients' perspective.